Laser surface treatment of porous ceramic substrate for application in solid oxide fuel cells - Dayang Salyani, Mahmod; Amir Azam, Khan; Magdalene, Andrew Munot; Glandut, N.; Labbe, Jean Claude (IOP Publishing Ltd, 2016)
Laser has offered a large number of benefits for surface treatment of ceramics due to possibility of localized heating, very high heating/cooling rates and possibility of growth of structural configurations only produced under non-equilibrium high temperature conditions. The present work investigates oxidation of porous ZrB2-SiC sintered ceramic substrates through treatment by a 1072 ± 10 nm ytterbium fiber laser. A multi-layer structure is hence produced showing successively oxygen rich distinct layers. The porous bulk beneath these layers remained unaffected as this laser-formed oxide scale and protected the substrate from oxidation. A glassy SiO2 structure thus obtained on the surface of the substrate becomes subject of interest for further research, specifically for its utilization as solid protonic conductor in Solid Oxide Fuel Cells (SOFCs).